The Usury-Free Social Movement and the Transformation of Islamic Economics: A Case Study of the Interest-Free Community in South Kalimantan - Alfinuri, Novita; Hafizah, Yulia; Haisy, Noorwahidah (At-Taradhi Jurnal Studi Ekonomi, 2025)
The widespread practice of riba (usury) through conventional financial systems—such as interest-based loans and consumer financing—has triggered a crisis of trust among Indonesian Muslims. This study aims to analyze the Masyarakat Tanpa Riba (MTR, or Society Without Usury) movement in South Kalimantan as a form of resistance against usurious systems and as an effort to build an economy based on Islamic values. Employing a qualitative case study approach, data were collected through in-depth interviews, participatory observations, and document analysis. The findings reveal that MTR fosters anti-riba awareness through a combination of scriptural (naqli) references, spiritual reflection, and systematic educational methods. Its core strategies include tiered seminars, commitment reinforcement through the Ultimate Life Changing (ULC) sessions, and the cultivation of group solidarity via emotionally charged forums such as What I Feel Like Expression (WIFLE). The community reinterprets riba practices in contexts such as leasing, mortgages, and pilgrimage financing with a literalist reading of Islamic texts. The MTR movement not only provides practical solutions to debt crises but also enables lifestyle transformation and shifts in business practices among its members. This study highlights how religious values can serve as a catalyst for community-driven economic transformation and ethical reform.   Praktik riba yang tersebar luas melalui sistem keuangan konvensional, termasuk pinjaman berbunga dan pembiayaan konsumtif, telah menimbulkan krisis kepercayaan di kalangan masyarakat Muslim Indonesia. Studi ini bertujuan untuk menganalisis gerakan sosial Masyarakat Tanpa Riba (MTR) di Kalimantan Selatan sebagai bentuk resistensi terhadap sistem ekonomi ribawi serta sebagai upaya membangun model ekonomi berbasis nilai-nilai Islam. Menggunakan pendekatan kualitatif dengan studi kasus, data diperoleh melalui wawancara mendalam, observasi partisipatif, dan telaah dokumen. Hasil penelitian menunjukkan bahwa gerakan MTR membangun kesadaran anti-riba melalui kombinasi dalil naqli, pengalaman spiritual, dan pendekatan edukatif yang sistematis. Strategi utama mereka meliputi seminar berjenjang, penguatan komitmen melalui forum ULC (Ultimate Life Changing), serta pembentukan solidaritas melalui ekspresi emosional kolektif seperti sesi What I Feel Like Expression (WIFLE). Komunitas ini juga mendefinisikan ulang praktik riba dalam konteks leasing, KPR, dan dana talangan dengan pendekatan yang lebih literal terhadap teks keagamaan. Gerakan MTR tidak hanya menawarkan solusi praktis atas krisis utang, tetapi juga membentuk transformasi gaya hidup dan pola bisnis anggotanya. Studi ini memperlihatkan bagaimana nilai religius dapat menjadi motor penggerak transformasi ekonomi berbasis komunitas dan spiritualitas.